COMBINATION OF STATE REGULATION OF HOUSING CONSTRUCTION AND MANAGEMENT OF THE RESTORATION OF ABANDONED HOUSING IN UKRAINE - Moroz, Volodymyr (Public Management and Policy, 2026)
The article examines the specific features of state regulation of housing construction and the restoration of Ukraine’s housing stock under wartime challenges and the needs of post-war reconstruction. It substantiates that the transformation of state housing policy is driven by the large-scale destruction of housing infrastructure, the increasing social vulnerability of the population, the growth of internal migration, and the need to develop comprehensive mechanisms for rebuilding the housing sector. The study analyzes the regulatory and legal framework of state policy in the field of housing construction, the restoration of damaged and destroyed housing, as well as the management of housing resources under crisis conditions. It is determined that the current regulatory system requires improvement through a combination of new construction instruments, reconstruction measures, and the reintegration of the existing housing stock into effective use. The current state of Ukraine’s housing stock is analyzed, and the main problems of its functioning under wartime conditions are outlined. It is established that, alongside the direct losses of housing infrastructure, the problems of affordable housing shortages, uneven territorial provision of housing resources, the growing needs of internally displaced persons, and the presence of a significant amount of abandoned or inefficiently used housing have become more acute. The article characterizes the mechanisms of international financial support for the restoration of Ukraine’s housing infrastructure, in particular, the instruments of the European Union and international financial institutions. It also analyzes the significance of the state program “eVidnovlennia” as a tool for compensation for damaged or destroyed housing and for stimulating the reconstruction of the housing stock. As a result of the study, a model is proposed for combining state regulation of housing construction with the management of the restoration of abandoned housing stock. This model provides for the integration of regulatory, institutional, and financial mechanisms of state policy and is aimed at increasing the efficiency of housing resource use in the process of Ukraine’s post-war reconstruction.